A multiscale approach to detect selection in nonmodel tree species: Widespread adaptation despite population decline in Taxus baccata L. (19th July 2019) - Mayol, Maria; Riba, Miquel; Cavers, Stephen; Grivet, Delphine; Vincenot, Lucie; Cattonaro, Federica; Vendramin, Giovanni G.; González‐Martínez, Santiago C.
Abstract: Detecting the molecular basis of local adaptation and identifying selective drivers is still challenging in nonmodel species. The use of purely population genetic approaches is limited by some characteristics of genetic systems, such as pleiotropy and polygenic control, and parallel evidence from phenotypic‐based experimental comparisons is required. In long‐lived organisms, the detection of selective pressures might also be precluded by evolutionary lag times in response to the environment. Here, we used the English yew to showcase an example of a multiscale integrative approach in a nonmodel species with limited plant and genomic resources. We combined information from two independent sources, phenotypes in a common environment and genomic data in natural populations, to investigate the signature of selection. Growth differences among populations in a common environment, and phenological patterns of both shoot elongation and male strobili maturation, were associated with climate clines, providing evidence for local adaptation and guiding us in the selection of populations for genomic analyses. We used information on over 25, 000 SNPs from c. 1, 200 genes to infer the demographic history and to test for molecular signatures of selection at different levels: SNP, gene, and biological pathway. Our results confirmed an overall demographic history of population decline, but we also found evidence for putative local adaptation at the molecular level. We identified or confirmed several candidate genes for positive and negative selection in forest trees, including the pseudo‐response regulator 7 (PRR7), an essential component of the circadian clock in plants. In addition, we successfully tested an approach to detect polygenic adaptation in biological pathways, allowing us to identify the flavonoid biosynthesis pathway as a candidate stress‐response pathway that deserves further attention in other plants. Finally, our study contributes to the emerging view that explaining contemporary standing genetic variation requires considering adaptation to past climates, especially for long‐lived trees.